Implementasi Teknik Graphic Match Cut oleh Animator dalam Video Animasi Motion Graphic “Rokok Elektrik Bukan Pilihan” - Farel Aditya; Rafi Admadyana; Toto Sugito; Encang Saepudin (BADAN PENERBIT STIEPARI PRESS, 2025)
The animated video “Rokok Elektrik Bukan Pilihan” is an educational work aiming to raise awareness among youth about the dangers of using electronic cigarettes. This project utilizes the graphic match cut technique as a visual strategy to strengthen continuity between scenes and smooth visual transitions. This study aims to analyze the effectiveness of the technique in enhancing educational message delivery through animated media. The method used is a production study with a descriptive qualitative approach through direct observation of the creative process from pre-production to post-production. The results indicate that the implementation of graphic match cut successfully creates a cohesive narrative flow, enhances emotional impact, and increases audience engagement in understanding the message content. These findings suggest that animation with appropriate visual approaches can serve as an effective and engaging medium for health education.